2008
DOI: 10.1111/j.1751-7176.2008.07837.x
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Effects of an Angiotensin Receptor Blocker on Health‐Related Quality of Life in Patients With High‐Normal Blood Pressure (Prehypertension) in the Trial of Preventing Hypertension (TROPHY)

Abstract: The Trial of Preventing Hypertension (TROPHY) demonstrated the feasibility of possibly reducing the incidence of hypertension with the angiotensin receptor blocker candesartan compared with placebo. The long‐term benefits of pharmacologic therapy in high‐normal blood pressure, or prehypertension are not known, and the long‐term effect on health‐related quality of life (HRQL) has not been determined. An analysis of covariance model was used to assess treatment differences from baseline in the HRQL scores using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Also, it showed that using Angiotensin converting enzyme inhibitors (ACEI) or Angiotensin receptors blockers (ARB) and using a combination therapy of Bblockers + Diuretics had high scores on all scales of SF-36. These results are similar to results found by other studies, [14,15] which found that Angiotensin-converting enzyme inhibitors and angiotensin II receptor antagonists may offer some advantage with regard to effects on cognitive function and sexual activity over other classes of medications while calcium channel blocker-based treatment regimen lowered HRQL more than other types of medications. Also, [12,16] showed that patient symptoms and HRQL improve with control of blood pressure measures with diuretics and other medications.…”
Section: Discussionsupporting
confidence: 90%
“…Also, it showed that using Angiotensin converting enzyme inhibitors (ACEI) or Angiotensin receptors blockers (ARB) and using a combination therapy of Bblockers + Diuretics had high scores on all scales of SF-36. These results are similar to results found by other studies, [14,15] which found that Angiotensin-converting enzyme inhibitors and angiotensin II receptor antagonists may offer some advantage with regard to effects on cognitive function and sexual activity over other classes of medications while calcium channel blocker-based treatment regimen lowered HRQL more than other types of medications. Also, [12,16] showed that patient symptoms and HRQL improve with control of blood pressure measures with diuretics and other medications.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is of translational relevance because drug-related side effects of continuous treatment could be reduced, whereas prehypertensive treatment is feasible (Julius et al, 2006). In addition, prolonged dose reduction during adulthood may result in fewer side effects and a reduced pharmacoeconomic burden (Williams et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, the potential preconditioning effects of combined prehypertensive and antihypertensive treatment separated by a period of drug holiday, in particular whether TPT may allow a dose reduction of AHT with consecutive reduction of antihypertensive side effects and costs, have been neglected. Investigating preconditioning in an experimental setting may help us to understand the value of TPT and to estimate the pharmacoeconomic relevance of this treatment strategy (Williams et al, 2008).The majority of animal models dealing with TPT used spontaneously hypertensive rats (SHR) (Berecek et al, 1984;Wu et al, 1994), which are characterized by late cardiac failure (Slama et al, 2004 ABBREVIATIONS: TROPHY, trial of preventing hypertension; TPT, transient prehypertensive treatment; AT1R, angiotensin II type 1 receptor; AHT, antihypertensive treatment; SHR, spontaneously hypertensive rats; SHHF/Mcc-fa cp , SHHF, spontaneous hypertensive heart-failure rats; RAS, renin-angiotensin system; ATRAP, AT1R signaling and receptor internalization; W/liter, wall/lumen ratio; TNF-␣, tumor necrosis factor-␣; MAP, mean arterial pressure; EDV, end-diastolic volume; HW/BW, heart weight/body weight; BNP, brain natriuretic peptide; GAPDH, glyceraldehyde-3-phosphate dehydrogenase. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…19 Follow-up analysis showed no significant between-group differences on quality-of-life measures, including either the physical or mental components of the short-form (SF)-36. 20 TROPHY's methods and results have been roundly criticized in several venues, with one editorialist going so far as to call the trial "a noble effort gone sour." 18 Although noting the evidence of risk reduction with candesartan, Kaplan and Ong pointed out that TROPHY findings were inconsistent with the natural history of prehypertension.…”
Section: Clinical Benefits Of Pharmacotherapy For Primary Preventionmentioning
confidence: 99%